IMPLEMENTATION OF VISA SERVICES AS IMMIGRATION POLICY DURING PANDEMIC OF COVID-19 - Bella Agustina Halimah (Journal of Administration and International Development, 2021)
At the end of 2019, the world was shocked by the invention of a new variant virus in Wuhan, laternamed Covid-19. This case has become a particular concern to the world, especially WHO, because the virus can cause fatalities, and the rate of transmission is very fast. Shortly after the invention, WHO declared Covid19 as a global pandemic. Each country is doing their best to prevent the Covid-19 virus from entering their country's territory, including in Indonesia. The Indonesian government then creates policies from all aspectsand fields to prevent and break thetransmission chain of Covid-19 cases. One of the fieldsthat played a roleis Immigration.Directorate General of Immigration, as one of the authorized institutions in the field of Immigration,has authority over all activities of people who entering and exiting the territory of Indonesia. During this Covid-19 pandemic, Indonesian Immigration has created new policies. One of the policies thathave been created is the policy about Visa services that are provided and applied to Foreign Nationals who will enter and stay in Indonesia. Immigration policy related to visas is continuously updated and applied according to the situation, conditions, and policies of the government to achieve one goal, which is preventing and breaking the transmission chain of Coronavirus in Indonesia.